2009
DOI: 10.1128/jb.01240-08
|View full text |Cite
|
Sign up to set email alerts
|

Indole Acts as an Extracellular Cue Regulating Gene Expression inVibrio cholerae

Abstract: Indole has been proposed to act as an extracellular signal molecule influencing biofilm formation in a range of bacteria. For this study, the role of indole in Vibrio cholerae biofilm formation was examined. It was shown that indole activates genes involved in vibrio polysaccharide (VPS) production, which is essential for V. cholerae biofilm formation. In addition to activating these genes, it was determined using microarrays that indole influences the expression of many other genes, including those involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
184
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(200 citation statements)
references
References 62 publications
10
184
3
3
Order By: Relevance
“…In Pseudomonas putida , signalling molecules such as indole enhances TtgGHI efflux pump that are relevant for antibiotic resistance (Molina‐Santiago et al ., 2014). The previous studies have reported that indole inhibits biofilm formation and suppresses the virulence of bacterial strains such as Staphylococcus aureus , Agrobacterium tumefaciens (Lee and Lee, 2010; Lee et al ., 2013, 2015a,b; Lee et al ., 2016) and Vibrio cholera (Mueller et al ., 2009). Likewise, indole derivatives such as 7‐fluoroindole, 7‐hydroxyindole, 3‐indolyl acetonitrile and 2‐aminobenzimidazoles have been reported to exhibit antimicrobial activities against pathogenic bacteria (Lee et al ., 2009, 2011, 2012, 2015a,b; Frei et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Pseudomonas putida , signalling molecules such as indole enhances TtgGHI efflux pump that are relevant for antibiotic resistance (Molina‐Santiago et al ., 2014). The previous studies have reported that indole inhibits biofilm formation and suppresses the virulence of bacterial strains such as Staphylococcus aureus , Agrobacterium tumefaciens (Lee and Lee, 2010; Lee et al ., 2013, 2015a,b; Lee et al ., 2016) and Vibrio cholera (Mueller et al ., 2009). Likewise, indole derivatives such as 7‐fluoroindole, 7‐hydroxyindole, 3‐indolyl acetonitrile and 2‐aminobenzimidazoles have been reported to exhibit antimicrobial activities against pathogenic bacteria (Lee et al ., 2009, 2011, 2012, 2015a,b; Frei et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, indole, which is prevalent in the gastrointestinal tract, has been proposed to act as an extracellular signal molecule influencing biofilm formation in a range of bacteria. In V. cholerae, indole has been shown to activate genes involved in VPS production that are essential for vps-dependent biofilm development (114). In E. coli O157:H7, indole has the opposite effect of reducing attachment to both abiotic surfaces and epithelial cells (8).…”
Section: Why Attach In the First Place?mentioning
confidence: 99%
“…Recently, indole has been identified as a signal molecule involved in the formation of biofilm by V. cholerae (Mueller et al 2009), controlling the vps genes which regulate the production of Vibrio polysaccharides that make up the bulk of a biofilm matrix. Several natural products (containing indole moieties) extracted from a Mediterranean gorgonian coral were shown to be effective at inhibiting the formation of biofilms by 3 marine bacteria (Penez et al 2011).…”
Section: Disruption Of Biofilms Through Inhibition Of Bacterial Signamentioning
confidence: 99%
“…Indole-producing bacteria also can inhibit the growth of pathogens (see antibacterial activity). As the genes controlled by indole are now characterised in V. cholerae (Mueller et al 2009), it will be of interest to test whether the alkaloids produced by marine organisms are capable of interfering with bacterial indole-mediated signalling.…”
Section: Disruption Of Biofilms Through Inhibition Of Bacterial Signamentioning
confidence: 99%